An investigation of the Four Area Curriculum Extension and Enrichment Model for Gifted Education as viewed through the Cartesian, Socialist and Deep Ecology epistemologies - Mentz, Hendrik Jeremy (School of Education, 2016)
Because giftedness is a complex, little understood concept which has become politicised, it was deemed necessary to evaluate the Four Area Curriculum Extension and Enrichment model in terms of three epistemological focuses: Cartesian, Socialist and Deep Ecology. Reasons for the selection of these three epistemologies are discussed after which the traditional Cartesian, homunculus view of giftedness is shown to be flawed and a case made for reconceptualizing giftedness to confirm its collective, socially constructed, immanent nature, grounded in the existential human condition. The rationale behind, and design of the Four Area model as reflected in the guide to schools is shown to reflect the Deep Ecology epistemology. The philosophical statement, goal and aims of the guide are shown as clashing with the Deep Ecology ideology. In order to avoid epistemological dissonance, a reformulated statement of intent for the Four Area model which merges the Cartesian, Socialist and Deep Ecology epistemologies into a unitary aim is suggested. The design, short-term success and appropriateness of each of the four Areas of provision are analyzed and evaluated in the light of critical theory as also questionnaires and annual reports completed by principals and co-ordinators. Modifications to aspects of the Four Area model are recommended which, it is argued, will give it greater contextual relevance and make it an appropriate medium for promoting giftedness for all South African pupils. Finally, it is argued that intelligence and genius should be viewed, not as personal capacities, nor as social constructs but metaphysically as a function of gathering complexity.